2021
DOI: 10.4103/ajns.ajns_458_20
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of multifocality in insular tumors: Multicentricity versus metastasis

Abstract: Background and Purpose: Multifocality and metastasis from insular glioma are extremely rare. Pathological insights and elaboration of the clinical course of this condition will contribute to their better understanding. Materials and Methods: Among 123 consecutively operated insular gliomas, 5 patients (4.2%) presented with a multifocal tumor. The clinico-radiological, histo-molecular, and treatment outcomes were noted and compared with the unifocal insular glioma cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Nevertheless, Esmaoglu et al [ 25 ] documented that adding dexmedetomidine 100 µg to the LA resulted in significant HR, systolic blood pressure, and diastolic blood pressure within the first two hours. Other studies [ 26 , 27 ] have reported marked bradycardia and hypotension following dexmedetomidine administration. Our research did not observe that we used a lower dose of dexmedetomidine (0.5 µg/kg).…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, Esmaoglu et al [ 25 ] documented that adding dexmedetomidine 100 µg to the LA resulted in significant HR, systolic blood pressure, and diastolic blood pressure within the first two hours. Other studies [ 26 , 27 ] have reported marked bradycardia and hypotension following dexmedetomidine administration. Our research did not observe that we used a lower dose of dexmedetomidine (0.5 µg/kg).…”
Section: Discussionmentioning
confidence: 93%